Posterior Reversible Encephalopathy Syndrome in Hypertensive Disorders of Pregnancy: Incidence and Clinical Predictors in a Prospective MRI-Based Study - Burak Arslan; Arif Güngören (Women’s Health and Multidisciplinary Research, 2026)
Background and Aim: Posterior reversible encephalopathy syndrome (PRES) is an important neurologic complication associated with hypertensive disorders of pregnancy. This prospective study aimed to determine the incidence of PRES in patients with preeclampsia, eclampsia, and HELLP syndrome and to identify associated clinical factors. Materials and Methods: This prospective observational study was conducted at a tertiary referral center between November 2019 and November 2020. Pregnant women diagnosed with preeclampsia, eclampsia, or HELLP syndrome were included. Cranial magnetic resonance imaging (MRI) was performed during the peripartum period. PRES was diagnosed based on characteristic radiologic findings consistent with vasogenic edema. Demographic and clinical characteristics were recorded. Factors associated with PRES were evaluated using univariate analysis and reported as odds ratios (ORs) with 95% confidence intervals (CIs). Results: Among 39 patients with hypertensive disorders of pregnancy, PRES was identified in 10 (25.6%) women. The prevalence of PRES was significantly higher in patients with eclampsia than in those with preeclampsia (71.4% vs. 14.3%, p=0.012). Seizure occurrence was strongly associated with the development of PRES (OR=8.67, 95% CI: [1.55–48.49]; p=0.011). Patients with PRES were younger and had longer hospital stays than those without PRES. No significant association was observed between hypertension and the development of PRES. Conclusion: PRES is not uncommon among patients with hypertensive disorders of pregnancy and occurs particularly frequently in patients with eclampsia. The presence of seizures was strongly associated with the development of PRES. Early MRI evaluation should be considered in patients presenting with neurologic symptoms to facilitate timely diagnosis and potentially reduce maternal neurologic morbidity.